Stability of ex vivo coagulation factor activity in never‐frozen and thawed refrigerated canine plasma stored for 42 days. Issue 2 (12th November 2021) - Chee, Weiqin; Sharp, Claire R.; Boyd, Corrin J.; Claus, Melissa A.; Smart, Lisa
Abstract: Objective: The primary objective of this study was to document coagulation factor activity in canine "NEVER‐FROZEN" and "THAWED" refrigerated plasma for the purposes of defining recommended expiration dates. We hypothesized that NEVER‐FROZEN and THAWED refrigerated plasma would maintain >50% activity of coagulation factors V (FV), VII (FVII), VIII (FVIII), IX (FIX), X (FX), and von Willebrand factor antigen (vWF) and a concentration of fibrinogen above the lower bound of the reference interval (>0.982 g/L) for greater than 14 days but less than 42 days. Design: Prospective laboratory‐based study. Setting: University teaching hospital blood bank. Animals: Ten canine plasma units derived from healthy client‐owned blood donors. Interventions: Serial sampling (days 0, 1, 3, 5, 7, 10, 14, 17, 21, 24, 28, 32, 35, 39, 42) from NEVER‐FROZEN and THAWED refrigerated canine plasma units was conducted for measurement of activities of FV, FVII, FVIII, FIX, FX, vWF, and fibrinogen concentrations using the ACL TOP 300. Plasma was defined as "suitable for transfusion" at a given time point if the entire 95% confidence interval for each factor was above 50% activity and above a fibrinogen concentration of 0.982 g/L. Measurements and main results: The lower bounds of the FVIII and vWF confidence intervals were above 50% up to and including day 32 for NEVER‐FROZEN refrigerated plasma and day 28 for THAWED refrigerated plasma. Confidence intervals for FV, FVII, FIX, and FX remained above 50% activity at all time points. The lower bound of the fibrinogen concentration was <0.982 g/L on day 39 for NEVER‐FROZEN refrigerated plasma and on day 35 for THAWED refrigerated plasma. Conclusions: Refrigerated canine plasma from these 10 dogs retained coagulation factor activity above the limit that we defined as suitable for transfusion for up to 32 days when NEVER‐FROZEN and 28 days when THAWED. Further studies should evaluate the clinical outcomes and effects on coagulation factor activity of dogs receiving refrigerated plasma transfusions.